The Legal Status Of Sustainable Development In The Nigerian Environmental Law - Okon, Emmanuel E. (Journal of Sustainable Development Law and Policy, 2025)
Sustainable development underpins environmental governance in all jurisdictions, but its legal status is still controversial. The major problem which Nigerian courts and policy-makers will continue to face when implementing and enforcing sustainable development in environmental governance is whether it is a moral or legal concept and, if it is the latter, whether it has metamorphosed into a legal principle or the rule of law having a normative value. This article argues that the legal status of sustainable development in Nigeria depends on which legal instrument it is incorporated and whether it is expressed in a general or specific mandatory language. Also, its legal status depends on the pronouncements of Nigerian courts on it. Methodologically, the qualitative content analysis is used to ascertain the legal status of sustainable development in the statutes and case law examined. In order to enhance the implementation and enforcement of sustainable development in the Nigerian environmental law, the conclusion of this article adopted as recommendations the latter part of its argument that sustainable development should be made an essential part of the right to life, the relevant constitutional provisions on the environmental should be amended to reflect it and, in addition, section 20 of the Constitution of the Federal Republic of Nigeria 1999 should be transferred to Chapter IV of the Constitution, which deals with fundamental human rights.